1993
DOI: 10.1099/00207713-43-4-640
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma canigenitalium sp. nov., Isolated from Dogs

Abstract: Ureaplasma strains isolated from dogs (Canis familiaris) were characterized and compared with the type strains of five previously described species of the genus Ureaphma, Ureuphmu urealyticum (isolated from humans), Ureaphma diversum (isolated from cattle), Ureaphma gallorale (isolated from chickens), Ureaplusm cati (isolated from cats), and Ureaphma felinum (isolated from cats). The canine strains hydrolyzed urea but not arginine or glucose, were membrane bound, lacked a cell wall, passed through 450-nm-pore-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…occur with any frequency in male dogs. Moreover, a direct relationship between these pathogens and clinical signs has not been fully documented and remains controversial (8,11,21). Our results clearly showed that cBD possesses broad antibacterial effects against the sexually transmitted disease pathogens used in the present study.…”
Section: Vol 73 2005supporting
confidence: 69%
See 2 more Smart Citations
“…occur with any frequency in male dogs. Moreover, a direct relationship between these pathogens and clinical signs has not been fully documented and remains controversial (8,11,21). Our results clearly showed that cBD possesses broad antibacterial effects against the sexually transmitted disease pathogens used in the present study.…”
Section: Vol 73 2005supporting
confidence: 69%
“…It has been suggested that eukaryotic cells are more resistant to the poreforming effects of defensins due to the presence of cholesterol in the cellular membrane (56). The lack of cBD killing effect may explain why Ureaplasma is commonly isolated from the canine genital tract, where it is present as normal microflora (21).…”
Section: Vol 73 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…U. felinum FT2-BT, U. cati F2T, and U. canigenitalium D6P-CT were all obtained from our laboratory stock cultures (5,6). All of the strains were grown aerobically in liquid medium at 37°C as described previously…”
mentioning
confidence: 99%
“…Since mycoplasmas can be found in the urogenital tract of healthy dogs, it can be difficult to determine whether they are the causal agent in dogs with genitourinary tract infections (Harasawa et al . ). Two case series reported isolating Mycoplasma species from 1·4 to 5·7% of dogs with urinary tract infections (Jang et al .…”
Section: Introductionmentioning
confidence: 97%